Communicable Diseases Intelligence Quarterly Report volume 32 issue 1 March 2008-whole issue - No authors listed (Communicable Diseases Intelligence, 2008)
Contents Tuberculosis notifications in Australia, 2006 Tuberculosis in Australia: bacteriologically confirmed cases and drug resistance, 2006: A report of the Australian Mycobacterium Reference Laboratory Network Invasive pneumococcal disease in Australia, 2006 Communicable Diseases Network Australia National Arbovirus and Malaria Advisory Committee annual report, 2006–07 Surveillance of antibiotic resistance in Neisseria gonorrhoeae in the WHO Western Pacific Region, 2006 Australian Paediatric Surveillance Unit annual report, 2006 Influenza viruses with reduced sensitivity to the neuraminidase inhibitor drugs in untreated young children Higher than expected seasonal influenza activity in Victoria, 2007 Enhanced surveillance for serious complications of influenza in children: role of the Australian Paediatric Surveillance Unit Absence of a Chlamydia trachomatis variant, harbouring a deletion in the cryptic plasmid, in clients of a sexually transmissible infection clinic and antenatal patients in Melbourne Rotavirus surveillance in Australia A norovirus outbreak associated with consumption of NSW oysters: implications for quality assurance systems The public health value of emergency department syndromic surveillance following a natural disaster School-based vaccinations delivered by general practice in rural north Queensland: an evaluation of a new human papilloma virus vaccination program OzFoodNet quarterly report, 1 October to 31 December 2007 Communicable Diseases Surveillance: Highlights for 4th quarter, 2007 (gastrointestinal disease, sexually transmitted diseases, vaccine preventable diseases, other bacterial infections) National Notifiable Diseases Surveillance System tables, 1 October to 31 December 2007 Laboratory Serology and Virology Reporting Scheme tables, 1 October to 31 December 2007 Australian Sentinel Practices Research Network, reporting period 1 October to 31 December 2007 Gonococcal surveillance, reporting period 1 July to 30 September 2007 HIV and AIDS surveillance, reporting period 1 April to 30 June 2007 HIV and AIDS surveillance, reporting period 1 July to 30 September 2007 Australian childhood immunisation coverage, 1 July to 30 September 2007 cohort, assessed as at 31 December 2007 National Enteric Pathogens Surveillance System, reporting period 1 October to 31 December 2007 Overseas brief, reporting period 1 October to 31 December 2007 (Chikungunya, cholera, dengue fever, Ebola haemorrhagic fever, influenza (avian), plague (bubonic), poliomyelitis, Rift Valley fever, tuberculosis) Communicable Diseases Intelligence instructions for authors Surveillance systems reported in CDI, 2008